The Effectiveness of “Only Few Left” in Triggering FOMO and Its Influence on Online Purchasing Decisions via TikTok Shop (Case Study: Generation Z in Palu City) - Kinsky, Niken Nazira; Rombe, Elimawaty (Dinasti International Journal of Education Management and Social Science, 2025)
This study examines the effectiveness of scarcity-based marketing strategies in triggering Fear of Missing Out (FOMO) and its impact on online purchasing decisions through TikTok Shop among Generation Z in Palu, Indonesia. This research employed a quantitative methodology with a descriptive-verification strategy. Data were collected from 150 Generation Z respondents who had shopped at TikTok Shop and were exposed to the limited quantity label, using a purposive sampling approach. Data analysis was conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The findings indicate that the minimum quantity remains, exerting a beneficial and significant influence on FOMO and purchase decisions. FOMO positively impacts purchase decisions and mediates the correlation between minimum availability and purchase choice. The combination of Only Few Left and FOMO explains 80.5% of the variation in online purchasing decisions. These findings confirm that real-time stock scarcity signals effectively trigger emotional responses and drive impulse buying behavior among Generation Z, thus providing practical implications for optimizing marketing strategies on social commerce platforms.